EVALUATION OF ANTICLASTOGENIC POTENTIAL OF CINNAMOMUM CASSIA BARK EXTRACT AGAINST ARSENIC GENOTOXICITY BY USING MICRONUCLEUS ASSAY IN MUS MUSCULUS CAUDAL ERYTHROCYTES - Sk, Ambasta; Ak, Adav; Uk, Sinha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The study was aimed to evaluate the anticlastogenic potential of ethanolic extract of Cinnamomum cassia against arsenic-induced genotoxicity. Methods: In the experiment, 30 animals were taken and divided into five groups and each group contains six animals. Group 1 was control and fed on tap water of Patna city while rest four (2, 3, 4, 5) groups were treated with 4 mg/kg body weight, per orally sodium arsenite for 8 weeks. Sodium arsenite pre-treated Groups 4 and 5 were followed by dose of 100 mg/kg body weight of 5% ethanolic solution of test plant bark extract for next 8 weeks (total duration of dosing 16 weeks). Caudal blood collected from each mouse by minor nick without their sacrifice and smeared blood was stained by double staining. Approximately, 2000 cells were scored by light microscopy to determine micronucleus (MN) frequency. The percentage of MN frequency was expressed in the terms of mean and standard deviation. Results: High index of MN frequency was observed in the Groups 2 and 3 while its frequency drastically reduced in Groups 4 and 5. The mean number of MN scored per 2000 cell were found to be 4.5, 23.5, 18.8, 10.5, and 9.66 in animal Groups 1, 2, 3, 4, 5,respectively. Conclusion: C. cassia may be effective drug in the area of preventive cancer or other kinds of diseases which lead to damage of genetic materials.